Colubrina limae (Rhamnaceae), a new species from seasonally dry tropical forests of Brazil - Figueira, Maurício; Schindler, Bianca; de V. Barbosa, Maria Regina; Giulietti, Ana Maria; Simon, Marcelo Fragomeni (Phytotaxa, 2024)
Colubrina limae (Rhamnaceae, Ziziphoid group, subgen. Colubrina, sect. Cowania) is described and illustrated as a new species. We provide information on its geographical distribution, habitat, phenology, and conservation status. A table with key morphological characters comparing C. limae with all Brazilian species of Colubrina and one similar species in section Cowania is provided. C. limae differs remarkably from its congeners by the presence of stipitate glands on the abaxial side of leaves, brochidodromous venation, inflorescences in fascicles, and longer (>25 mm) fruit pedicels. It does have some morphological similarities with C. elliptica, a species from Central and northern South America. The new species is found mainly in the understory of seasonally dry forests associated with limestone outcrops; only two populations are recorded in the municipality of Januária in Minas Gerais state, Brazil.